Attitudes of Primery School Students in Amman Towards Gymnastics - A’mir, Omar (Dirasat: Educational Sciences, 2020)
The objective of the study is to identify the attitudes of the students of primary schools in Amman- Jordan towards the exercise of gymnastics in light of some variables; namely gender, grade and type of school (public, private, UNRWA). The subjects of study were 694 students randomly selected from the schools. The participants were asked to fill in a questionnaire that measures their attitudes towards gymnastics. The questionnaire consists of (41) paragraphs distributed into (5) fields: cooperation, athletic and psychological excellence, physical health and fitness. The results indicated that the attitude of the primary school students in the city of Amman towards gymnastics was negative, and there were no statistically significant differences due to grade, gender, and school type. In light of the results of the study, the researcher recommends the need for raising awareness of the importance of gymnastics among students by highlighting its features and aesthetic aspects, in addition to the need for serious work to provide the equipments for gymnastic exercises for schools, especially public and UNRWA schools.